How does urban blue space affect human well-being? A study based on the stimulus-organism-response theory - Pei Lu; Pei Lu; Norazmawati Md. Sani; Yuan Li; Yuan Wang (Frontiers in Psychology)
With rapid urbanization and social change, mental health issues have surged. Urban blue spaces (UBSs) offer a potential tool to increase well-being, yet the way in which sensory stimuli shape landscape perception and well-being remains underexplored. Intergenerational integration, a crucial aspect of well-being, refers to shared experiences and social interactions among different age groups, improving cognition and reducing loneliness. However, the role of UBSs in facilitating such interactions remains insufficiently studied. This research, grounded in the Stimulus-Organism-Response (S-O-R) framework, examines how perceived multisensory stimuli (visual, auditory, olfactory, and tactile) influence landscape perception and well-being. Structural equation modeling (SEM) of survey data (n = 532) reveals that perceived visual, auditory, and tactile stimuli significantly enhance landscape perception and well-being, while olfactory stimuli have no significant effect. Landscape perception mediates the relationship between visual, auditory, and tactile stimuli and well-being, but not for olfactory stimuli. These findings underscore the importance of optimizing sensory environments in UBSs to enhance psychological restoration. The study provides empirical insights for urban planners and policymakers, advocating for nature-based strategies that enhance visual aesthetics, maintain site quality, integrate natural soundscapes, and improve water accessibility to maximize restorative benefits and foster intergenerational inclusion.